2019
DOI: 10.3390/nu11112682
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of Strategies to Optimize Vitamin D Status in Germany, a Population with a Western Diet

Abstract: During the last decade, our scientific knowledge of the pleiotropic biological effects of vitamin D metabolites and their relevance to human health has expanded widely. Beyond the well-known key role of vitamin D in calcium homeostasis and bone health, it has been shown that vitamin D deficiency is associated with a broad variety of independent diseases, including several types of cancer, and with increased overall mortality. Moreover, recent findings have demonstrated biological effects of the vitamin D endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 125 publications
0
7
0
Order By: Relevance
“…Similar calculations could and should be done for more recent time periods as soon as more up-to-date cancer mortality data become available, taking recent changes in fortification policies into account. For example, fortification was limited to margarine in Germany previously [ 26 ] but since recently, fortified milk and cereal-, soy-, or almond-based drinks are available. Due to demographic changes and the increasing proportion of elderly people in Europe, the preventive potential of food fortification is expected to increase in future decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar calculations could and should be done for more recent time periods as soon as more up-to-date cancer mortality data become available, taking recent changes in fortification policies into account. For example, fortification was limited to margarine in Germany previously [ 26 ] but since recently, fortified milk and cereal-, soy-, or almond-based drinks are available. Due to demographic changes and the increasing proportion of elderly people in Europe, the preventive potential of food fortification is expected to increase in future decades.…”
Section: Discussionmentioning
confidence: 99%
“…Fish consumption is also low and we can assume that for the majority of the population the alimentary vitamin D intake is generally scarce.” [ 48 ] Croatia “(…) despite the fact that the margarines are vitamin D fortified and some fortified dairy products are available, none of them contributes to [a] high vitamin D share in the diet.” [ 49 ] Cyprus No mandatory fortification (corr. with Cypriotic Public Health Authority, Sept. 21, 2020) Czech Republic “Moreover, there is no mandatory and only minimal voluntary vitamin D food fortification in the Czech Republic.” [ 50 ] Denmark Allowed, not mandatory, rarely done [ 51 ] Estonia Allowed but not mandatory [ 52 ] Finland Mass fortification of milk, margarine/fat spread; fortification of selected brands for yoghurt, orange juice, plant-based milk, bread, cereals 1 [ 53 ] ++ France Allowed but not mandatory [ 54 ] Germany No mandatory fortification + previously largely not allowed [ 26 ] Greece No fortification policy [ 55 ] Hungary “Because the typical Hungarian diet contains little vitamin D and food is not fortified, the vast majority of vitamin D is formed in the skin by ultraviolet-B (UVB) radiation.” [ 5...…”
Section: Introductionmentioning
confidence: 99%
“…In the face of this inconsistences, our study recommends that the increase in 25(OH)D serum concentration occur by diet (greater consumption of source foods) as well as by exposure to the sun (5–30 min, two to three times a week between the times of 10 am to 3 pm). Is that studies have shown that the simple exposure of some areas of the body (hands, arms and face) to the sun that produces a minimal erythema , is equivalent to a dietary intake of 1000 international units (IU) of vitamin D ( Brazilian Society of Dermatology, 2013 , Engelsen, 2010 , Saternus et al, 2019 ), a higher value than that recommended by the Recommended Dietary Allowances (RDA) ( Institute of Medicine, 2011 ), which is 600 IU/day for individuals aged 51–70 years and 800UI/day for those over 80 (by diet).…”
Section: Discussionmentioning
confidence: 99%
“…While the energy requirements of older adults tend to decrease compared with those for younger people, micronutrient needs remain similar or are even higher ( 17–20 ). Moreover, requirements for specific nutrients such as vitamin D and long-chain n–3 PUFAs are in a range unlikely to be met by the diet alone ( 21 ). Even in affluent countries, inadequate status or deficiencies in a range of micronutrients are observed in a significant proportion of the older population ( 22 ).…”
Section: Specific Challenges For Older Adults To Achieve Adequate Int...mentioning
confidence: 99%